(untitled) (Revista horizonte, 2015)
The study aim was to observe the behavioral change produced by a regular physical education program in a group of children. Most of them had mild to moderate intellectual disability, and one had Down’s Syndrome. They all attended a special school in the city of Osorno that included vocational rehabilitation. Five children with ages between 10 and 13 years-old. The physical education program implemented included twelve weeks of 60-minute sessions, twice a week. We used a) checklist: this instrument allowed the assessment of student’s performance in every lesson. b) observation log: where the most relevant aspects of each lesson were registered. c) interviews: each child gave their opinion about the physical education lessons. Results shown that children liked their physical education lessons, and they said they would like to have them again, since they were entertaining and they had positive feeling towards physical education activities. One of the most relevant points is that they feel that the lessons contributed to build respect among themselves.